Analisis Bibliometrik Tren Topik Penelitian pada Artikel Ilmiah Dosen Fakultas Rumpun Kesehatan Universitas Padjadjaran Tahun 2016 – 2020 - Marni, Ziani; Erwina, Wina; Rohman, Asep Saeful (Jurnal FPPTI, 2023)
Knowledge mapping in the field of health science is very important to do because it helps the lives of many people. The large number of scientific articles published by Universitas Padjadjaran lecturers in the health sector has not been accompanied by mapping of research topic trends. The aim of this research is to determine trends in research topics in scientific articles by lecturers at the Faculty of Health, Universitas Padjadjaran and to determine the position of research topics that have been conducted on health topics in the world and in Indonesia. The research method used is the bibliometric method with a quantitative approach using Co-word analysis based on the presence of keywords available in each scientific article. The research results show that the trend of research topics in scientific articles by health faculty lecturers in 2016-2020 is Children, Knowledge, and Breast cancer. The research focus of health faculty lecturers in 2016-2019 was on the health of children, women or mothers, and adolescent health, then the research focus shifted in 2019-2020, namely regarding the Covid-19 virus. A small number of research topic trends carried out by health faculty lecturers are in line with world and Indonesian health topics according to the World Health Organization. Trends in research topics and research topics that are still little discussed can become references and recommendations for further research in the health sector.